Imagination and cinema: the notion of anthropos from the figure of the spectator - Ignacio Riffo (2019)
The present work is presented as an approach between the notion of the imaginary with the theory of the film viewer, formulated in 1956 by Edgar Morin, in his classic text The cinema or the imaginary man and enlarged by Francesco Casetti with the thesis of the enunciation in the cinema. In this way, the main objective of this article is to capture theoretical bases from the reflection of both conceptualizations. Thus, this initiatory work aims to be an epistemological contribution to future research projects. For this, at the methodological level, an initial theoretical path is developed that has its anchor -and its respective critical reading- in the contributions of Gilbert Durand and Cornelius Castoriadis, in the permanent concern of both for “drawing” those elements inherent in anthropos that allow the construction of their historical-social environment from subjectivity. The latter conceived as intrinsic peculiarity to the human being. It is concluded that through an artificial-imaginary state the viewer feels close and is able to recognize the reality of the images that the big screen offers him, coming into direct contact with his fantasies, fears and dreams. In other words, here the double dimension of the film is observed as an artifact and as a subjective experience.